2006
DOI: 10.1111/j.1464-5491.2006.01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Is neighbourhood deprivation a risk factor for gestational diabetes mellitus?

Abstract: These data suggest that the neighbourhood context in which women live has no impact on the risk of GDM. Diabet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…The lack of studies on LGA and neighborhood deprivation prevents comparison of our results for this outcome to other study populations, but a positive association is consistent with the theory that neighborhood deprivation might promote obesity and lead to LGA. Pathways leading to LGA may include lack of access to nutritious food or opportunities for exercise in disadvantaged neighborhoods (Diez Roux and Mair, 2010; Schempf, et al, 2009; Daniel, et al, 2008; Culhane and Elo, 2005), creating environments that promote obesity and diabetes (Vinikoor-Imler, et al, 2011; Elo, et al, 2009; Metcalfe, et al, 2011), which in turn contribute to accelerated fetal growth (Yessoufou and Moutairou, 2011; Boney, et al, 2005; Janghorbani, et al, 2006; Clausen, et al, 2006; Baptiste-Roberts, et al, 2012; Lu, et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of studies on LGA and neighborhood deprivation prevents comparison of our results for this outcome to other study populations, but a positive association is consistent with the theory that neighborhood deprivation might promote obesity and lead to LGA. Pathways leading to LGA may include lack of access to nutritious food or opportunities for exercise in disadvantaged neighborhoods (Diez Roux and Mair, 2010; Schempf, et al, 2009; Daniel, et al, 2008; Culhane and Elo, 2005), creating environments that promote obesity and diabetes (Vinikoor-Imler, et al, 2011; Elo, et al, 2009; Metcalfe, et al, 2011), which in turn contribute to accelerated fetal growth (Yessoufou and Moutairou, 2011; Boney, et al, 2005; Janghorbani, et al, 2006; Clausen, et al, 2006; Baptiste-Roberts, et al, 2012; Lu, et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LGA is of growing importance as prevalence of two major LGA risk factors – obesity and diabetes (Yessoufou and Moutairou, 2011; Boney, et al, 2005; Lu, et al, 2001) – continues to increase. Individual risk factors for birth outcomes are shaped by environmental context (Hogan, et al, 2001), and neighborhood deprivation is associated with obesity in adult men and women (Pearson, et al, 2014; Bell, et al, 2014), overweight in the first trimester of pregnancy (Clausen, et al, 2006), and gestational diabetes (Clausen, et al, 2006; Janghorbani, et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…These studies cannot easily be compared because of different definitions of socioeconomic status, but three studies have used indexes of relative deprivation of the area of residence of the women as in the present study. Two found no association (14,18), and one showed that living in an area of deprivation was positively associated with GDM (19). Other factors used to determine socioeconomic status were public or private health care sector (public sector increased association with GDM) (15), income, health insurance, residential zip code (no association) (20), education and current employment (inverse relationship, as in the present study) (13).…”
Section: Risk Factors For Gdmmentioning
confidence: 96%
“…The Australian Institute for Health and Welfare estimates that women in the most disadvantaged socioeconomic group have double the rates of obesity of those in the most advantaged group (21), and obesity is a recognized risk factor for GDM. The lack of data on pregestational weight or BMI of women is a limitation of this study but not unique to studies reporting the association of socioeconomic status with GDM (14,18,20). However, in those studies in which an adjustment for maternal weight was made, the inverse association with socioeconomic status was still evident (13,15,19).…”
Section: Risk Factors For Gdmmentioning
confidence: 98%
See 1 more Smart Citation